Pembuatan Briket Berbahan Arang Bambu dan Batok Kelapa sebagai Energi Alternatif - Muhammad Faisal; Hasbi Assiddiq; Jeffry Anggara; Husni Mubarak; Indra; Wisnu Khawirian (Infotekmesin, 2026)
The utilization of biomass as a renewable energy source represents a strategic alternative to reduce dependence on fossil fuels while promoting the sustainable use of organic waste. This study aims to evaluate the effect of varying ratios of bamboo charcoal and coconut shell charcoal, with coconut husk charcoal and binder composition kept constant, on the combustion characteristics of biomass briquettes, including ignition time, burning duration, and maximum combustion temperature. The research was conducted experimentally through biomass pyrolysis at a temperature of 300 °C for 10 hours, followed by material mixing, briquette molding, and combustion testing. The results indicate that variations in raw material composition significantly influence briquette combustion behavior. Briquettes with higher bamboo charcoal content exhibit faster ignition, whereas those dominated by coconut shell charcoal produce longer burning duration and higher combustion temperatures. The observed combustion behavior is qualitatively discussed based on differences in biomass characteristics as reported in the literature. These findings demonstrate that blending biomass with different combustion properties can achieve more balanced briquette performance.